A multi-period MILP model for the investment and design planning of a national-level complex renewable energy supply system. (October 2019) - Han, Seulki; Kim, Jiyong
Abstract: This study presents a comprehensive approach to plan and analyze strategic investment for the design of an integrated renewable energy source-based energy supply system. Initially, the renewable energy source-based energy supply system superstructure was generated, which included 1) different energy sources (wind, solar, and biomass), 2) various energy facilities (for production, storage, and transportation), and 3) three types of final energy demand (electricity, hydrogen, and liquid fuel). A network optimization model was then developed using a mixed integer linear programming. The optimization model was used to determine the investment timing and allocation to the underlying energy supply system, which includes the type and quantity of utilized renewable sources, in addition to the timing of installation, number and location and of energy facilities installed. The capability of the proposed approach is validated through a case study of future Korea. As a result, we identified the optimal configuration and the investment timing of a complex renewable energy supply system, which was determined by regional resource potentials and cost-effectiveness of the involved technologies. The case study results can be used as a guideline to support decision-making of energy industry stakeholders and government policymakers in the strategic planning of a sustainable energy system. Highlights: A new planning approach for a complex renewable energy system is proposed. An optimization model to maximize the net present value is presented. System configurations change to meet energy annual demand with minimum cost. Renewable source potential and land cost vitally affect system configuration.